Impact of the Introduction of Rotavirus Vaccine on Hospital Admissions for Diarrhea Among Children in Kenya: A Controlled Interrupted Time-Series Analysis. (23rd September 2019) - Otieno, Grieven P; Bottomley, Christian; Khagayi, Sammy; Adetifa, Ifedayo; Ngama, Mwanajuma; Omore, Richard; Ogwel, Billy; Owor, Betty E; Bigogo, Godfrey; Ochieng, John B; Onyango, Clayton; Juma, Jane; et al.
Abstract: Background: Monovalent rotavirus vaccine, Rotarix (GlaxoSmithKline), was introduced in Kenya in July 2014 and is recommended to infants as oral doses at ages 6 and 10 weeks. A multisite study was established in 2 population-based surveillance sites to evaluate vaccine impact on the incidence of rotavirus-associated hospitalizations (RVHs). Methods: Hospital-based surveillance was conducted from January 2010 to June 2017 for acute diarrhea hospitalizations among children aged <5 years in 2 health facilities in Kenya. A controlled interrupted time-series analysis was undertaken to compare RVH pre– and post–vaccine introduction using rotavirus-negative cases as a control series. The change in incidence post–vaccine introduction was estimated from a negative binomial model that adjusted for secular trend, seasonality, and multiple health worker industrial actions (strikes). Results: Between January 2010 and June 2017 there were 1513 and 1652 diarrhea hospitalizations in Kilifi and Siaya; among those tested for rotavirus, 28% (315/1142) and 23% (197/877) were positive, respectively. There was a 57% (95% confidence interval [CI], 8–80%) reduction in RVHs observed in the first year post–vaccine introduction in Kilifi and a 59% (95% CI, 20–79%) reduction in Siaya. In the second year, RVHs decreased further at both sites, 80% (95% CI, 46–93%) reduction in Kilifi and 82% reduction in Siaya (95% CI. 61–92%); this reduction was sustained at both sites into the third year. Conclusions: A substantial reduction in RVHs and all-cause diarrhea was observed in 2 demographic surveillance sites in Kenya within 3 years of vaccine introduction. Abstract : Following the national introduction of the rotavirus vaccine in Kenya, our impact evaluation across 2 surveillance sites indicates a substantial reduction in childhood hospitalization due to rotavirus-associated and all-cause severe diarrhea.